Modified catalyst for catalyzing toluene combustion and preparation method and application thereof

The Ce-doped perovskite LaCoO3 catalyst was prepared through hydrothermal prefabrication and MOF material template methods, which solved the problems of insufficient activity, stability and catalytic performance of materials under low temperature conditions in the existing technology, and achieved efficient toluene catalysis. combustion.

CN119327469APending Publication Date: 2025-01-21JIANG SU ZHONG CHE YUN HUI KE JI YOU XIAN GONG SI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411457252.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The prior art has problems in the catalytic combustion of toluene, which are insufficient in the activity, stability and catalytic performance of materials under low temperature conditions.

Method used

The water thermal prefabricated and MOF materials are used as a sacrifice template to prepare catalysts. The catalysts with a three -dimensional ellipotoscular structure and oxygen space are formed through the CE doped olty lyric LACOO3.

Benefits of technology

The activity, stability and thermal stability of the catalyst are significantly improved, especially the catalytic performance of toluene is excellent under low temperature conditions, and the reaction efficiency is high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119327469A_ABST
    Figure CN119327469A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a modified catalyst for catalyzing toluene combustion, which comprises the following steps: dissolving cobalt acetate tetrahydrate and lanthanum acetate tetrahydrate in 70ml of ethylene glycol, adding urea, and hydrothermally preparing an intermediate; the preparation method comprises the following steps: mixing N, N-dimethylformamide, ethanol and water to obtain a mixed solution A; adding the intermediate and 2, 5-dihydroxyterephthalic acid into the mixed solution A, stirring, adding cerium nitrate hexahydrate, and carrying out ultrasonic dispersion to obtain a homogeneous mixed solution B; transferring the homogeneous-phase mixed solution B into a hydrothermal kettle for secondary hydrothermal treatment, preserving heat, cooling, filtering and washing with ethanol, drying in vacuum, and calcining to obtain a catalyst sample Ce-LaCoO3-MOF. The catalyst is prepared by taking MOF as a precursor, a stable three-dimensional ellipsoidal perovskite structure of the catalyst is reserved, and oxygen vacancies are introduced by doping Ce, so that the activity, stability and thermal stability of the catalyst are remarkably improved. Therefore, the catalyst shows higher reaction efficiency in a toluene catalytic combustion process, and particularly shows excellent catalytic performance under a low-temperature condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of toluene catalysis, and in particular to a modified catalyst for catalyzing toluene combustion and a preparation method and application thereof. Background Art

[0002] Toluene is an important volatile organic compound (VOC), and its emission has great harm to the environment and human health. Therefore, how to effectively remove toluene from the air has become a research hotspot. In the prior art, metal organic framework materials (MOFs) are widely used in the fields of toluene adsorption and catalytic combustion due to their highly ordered pore structure and adjustable surface chemical properties. However, existing MOF materials and catalysts still have many shortcomings in practical applications.

[0003] For example, patent CN115703887A discloses a Zn-MOF-74 metal organic framework material. Although the material has a certain adsorption capacity for toluene at room temperature and pressure, in actual applications, toluene cannot be further rendered harmless after being adsorbed, which limits the wide range of its use scenarios.

[0004] Patent CN111686754A proposes a non-precious metal catalyst for catalytic combustion of volatile organic compounds and a preparation method thereof. Although it has certain advantages in reducing costs and improving catalytic performance, the article does not mention the stability of the catalyst, making its reliability in long-term use questionable.

[0005] In addition, patent CN108262049A discloses a modified low-temperature SCO denitrification catalyst and its preparation method. Although the catalyst adopts the manganese-cobalt-based MOF template sacrificial method, the crystal morphology is not additionally regulated during its preparation, which makes it difficult to optimize the specific surface area and pore structure of the material. At the same time, this technology is only applied to denitrification catalytic NO oxidation, and has failed to prove its catalytic combustion performance for toluene at low temperatures.

[0006] In view of the above shortcomings, the present invention aims to provide a new type of catalytic material to overcome the limitations of the prior art in the catalytic combustion of toluene, especially to improve the activity and stability of the material under low temperature conditions and the catalytic performance of toluene. Summary of the invention

[0007] The invention discloses a modified catalyst for catalyzing toluene combustion, a preparation method and an application thereof, and is used to solve relevant technical problems in the background technology.

[0008] The technical solution provided by the present invention is as follows: a method for preparing a modified catalyst for catalyzing toluene combustion, comprising the following steps:

[0009] Step S1, dissolving cobalt acetate tetrahydrate and lanthanum acetate tetrahydrate in 70 ml of ethylene glycol, adding urea, stirring for 30 minutes, and transferring to a hydrothermal kettle; keeping warm in an oven for a certain period of time, washing by ethanol centrifugation after cooling, and drying to obtain an intermediate;

[0010] Step S2, mixing N,N-dimethylformamide, ethanol and water to obtain a mixed solution A;

[0011] Step S3, adding the intermediate and 2,5-dihydroxyterephthalic acid to the mixed solution A and stirring, then adding cerium nitrate hexahydrate and performing ultrasonic dispersion to obtain a homogeneous mixed solution B;

[0012] Step S4, transferring the homogeneous mixed solution B to a hydrothermal kettle, keeping it warm in an oven for a certain period of time, cooling it to room temperature, filtering and washing it with ethanol; after vacuum drying, sending it to a muffle furnace for calcination to obtain a catalyst sample Ce-LaCoO3-MOF.

[0013] In one embodiment, in steps S1-S3, the molar ratio of cobalt acetate tetrahydrate, lanthanum acetate tetrahydrate, cerium nitrate hexahydrate, and 2,5-dihydroxyterephthalic acid is 1:(1-y):y:4:1 (y=0.1-0.3).

[0014] In one embodiment, the amount of cobalt acetate tetrahydrate is 0.1 times the mass of the homogeneous mixed solution B.

[0015] In one embodiment, in step S1, the oven is kept at 180° C. for 12 hours.

[0016] In one embodiment, in step S2, the volume ratio of N,N-dimethylformamide, ethanol and water is 8:1:1.

[0017] In one embodiment, in step S3, ultrasonic dispersion is performed for 30 minutes.

[0018] In one embodiment, in step S4, the oven is kept at 130° C. for 24 hours.

[0019] In one embodiment, in step S4, vacuum drying is performed at 70° C. for 12 hours, and calcination is performed at 400° C. for 6 hours.

[0020] A modified catalyst for catalyzing the combustion of toluene, which is suitable for being prepared by the preparation method of the modified catalyst.

[0021] A modified catalyst for catalyzing the combustion of toluene, and its application in catalyzing the combustion of toluene at low temperature.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The present invention adopts a method of hydrothermal prefabrication and using MOF materials as sacrificial templates, so that the prepared catalyst retains the three-dimensional ellipsoidal stacked perovskite structure under high-temperature calcination, preferentially exposes the most active 111 crystal plane, and inherits the large specific surface area characteristics and highly defective structure of the MOF precursor, which is conducive to overcoming mass transfer resistance and improving the adsorption characteristics of VOCs, thereby having excellent catalytic performance.

[0024] (2) The present invention modifies the perovskite LaCoO3 by Ce doping, causing its lattice expansion and distortion, causing it to transform from a rhombic phase to a cubic phase, which is conducive to the random distribution of oxygen vacancies, improves the mobility of oxygen ions, and improves the adsorption of gas-phase oxygen. 1.675 The synergistic effect of / LaCoO3 enhances the catalytic activity towards toluene at low temperatures and the overall stability of the catalyst.

[0025] (3) The present invention uses MOF as a precursor to prepare the catalyst, retains the stable three-dimensional ellipsoidal perovskite structure of the catalyst, and introduces oxygen vacancies by Ce doping, which significantly improves the activity, stability and thermal stability of the catalyst. This makes the catalyst show higher reaction efficiency in the catalytic combustion of toluene, especially showing excellent catalytic performance under low temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is the XRD pattern of the sample obtained in Example 1 of the present invention;

[0027] Figure 2 is a SEM image of the sample obtained in Example 1 of the present invention;

[0028] Figure 3 It is a comparison chart of the removal efficiency of toluene by the samples obtained from various embodiments of the present invention and comparative examples;

[0029] Figure 4 This is a graph showing the removal efficiency of toluene by the sample obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several changes and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0031] Example 1

[0032] 3g of cobalt acetate tetrahydrate and 3.74g of lanthanum acetate tetrahydrate were dissolved in 70ml of ethylene glycol (EG), 2.89g of urea was added, and after stirring for 30min, the mixture was transferred to a hydrothermal kettle and kept in an oven at 180℃ for 12h. After cooling, the mixture was washed by centrifugation with ethanol. After drying, the intermediate was mixed with 2.39g of 2,5-dihydroxyterephthalic acid (DHTA), and dissolved in a mixed solution A of 24ml N,N-dimethylformamide (DMF), 3ml of ethanol, and 3ml of ultrapure water. 1.05g of cerium nitrate hexahydrate was added, and ultrasonic dispersion was performed for 30min to form a homogeneous solution B. The homogeneous solution B was then transferred to a hydrothermal kettle and kept in an oven at 130℃ for 24h. After cooling to room temperature, the mixture was filtered and washed with ethanol, and then kept in a vacuum drying oven at 70℃ for 12h. Finally, the mixture was calcined in a muffle furnace at 400℃ for 6h to obtain sample Ce. 0.2 -La 0.8 CoO3-MOF.

[0033] Example 2

[0034] 3g of cobalt acetate tetrahydrate and 3.27g of lanthanum acetate tetrahydrate were dissolved in 70ml of ethylene glycol (EG), 2.89g of urea was added, and after stirring for 30min, the mixture was transferred to a hydrothermal kettle and kept in an oven at 180℃ for 12h. After cooling, the mixture was washed by centrifugation with ethanol. After drying, the intermediate was mixed with 2.39g of 2,5-dihydroxyterephthalic acid (DHTA), dissolved in a mixed solution A of 24ml N,N-dimethylformamide (DMF), 3ml of ethanol, and 3ml of ultrapure water, and 1.57g of cerium nitrate hexahydrate was added. The mixture was ultrasonically dispersed for 30min to form a homogeneous solution B. The homogeneous solution B was then transferred to a hydrothermal kettle and kept in an oven at 130℃ for 24h. After cooling to room temperature, the mixture was filtered and washed with ethanol, and then kept in a vacuum drying oven at 70℃ for 12h. Finally, the mixture was calcined in a muffle furnace at 400℃ for 6h to obtain the sample Ce. 0.3 -La 0.7 CoO3-MOF.

[0035] Example 3

[0036] 3g of cobalt acetate tetrahydrate and 4.21g of lanthanum acetate tetrahydrate were dissolved in 70ml of ethylene glycol (EG), 2.89g of urea was added, and after stirring for 30min, the mixture was transferred to a hydrothermal kettle and kept in an oven at 180℃ for 12h. After cooling, the mixture was washed by centrifugation with ethanol. After drying, the intermediate was mixed with 2.39g of 2,5-dihydroxyterephthalic acid (DHTA) and dissolved in a mixed solution A of 24ml N,N-dimethylformamide (DMF), 3ml of ethanol, and 3ml of ultrapure water. 0.52g of cerium nitrate hexahydrate was added and ultrasonically dispersed for 30min to form a homogeneous solution B. The homogeneous solution B was then transferred to a hydrothermal kettle and kept in an oven at 130℃ for 24h. After cooling to room temperature, the mixture was filtered and washed with ethanol, and then kept in a vacuum drying oven at 70℃ for 12h. Finally, the mixture was calcined in a muffle furnace at 400℃ for 6h to obtain sample Ce. 0.1 -La 0.9 CoO3-MOF.

[0037] Comparative Example 1

[0038] 3g of cobalt acetate tetrahydrate and 3.74g of lanthanum acetate tetrahydrate were dissolved in 70ml of ethylene glycol (EG), 2.89g of urea was added, and after stirring for 30min, they were transferred to a hydrothermal kettle, kept in an oven at 180℃ for 12h, cooled, centrifuged and washed with ethanol, and dried. The intermediate was mixed with 2.39g of 2,5-dihydroxyterephthalic acid (DHTA), dissolved in a mixed solution A of 24ml N,N-dimethylformamide (DMF), 3ml of ethanol, and 3ml of ultrapure water, and ultrasonically dispersed for 30min to become a homogeneous solution B. Subsequently, the homogeneous solution B was transferred to a hydrothermal kettle and placed in an oven at 130℃ for 24h. After cooling to room temperature, it was filtered and washed with ethanol, then placed in a vacuum drying oven at 70℃ for 12h, and finally placed in a muffle furnace for calcination at 400℃ for 6h to obtain the sample LaCoO3-MOF.

[0039] Comparative Example 2:

[0040] 3g of cobalt acetate tetrahydrate and 2.34g of lanthanum acetate tetrahydrate were dissolved in 70ml of ethylene glycol (EG), 2.89g of urea was added, and after stirring for 30min, the mixture was transferred to a hydrothermal kettle and kept in an oven at 180℃ for 12h. After cooling, the mixture was washed by centrifugation with ethanol. After drying, the intermediate was mixed with 2.39g of 2,5-dihydroxyterephthalic acid (DHTA), dissolved in a mixed solution A of 24ml N,N-dimethylformamide (DMF), 3ml of ethanol, and 3ml of ultrapure water, and 2.61g of cerium nitrate hexahydrate was added. The mixture was ultrasonically dispersed for 30min to form a homogeneous solution B. The homogeneous solution B was then transferred to a hydrothermal kettle and kept in an oven at 130℃ for 24h. After cooling to room temperature, the mixture was filtered and washed with ethanol, and then kept in a vacuum drying oven at 70℃ for 12h. Finally, the mixture was calcined in a muffle furnace at 400℃ for 6h to obtain sample Ce. 0.5-La 0.5 CoO3-MOF.

[0041] Sample Ce prepared in Example 1 0.2 -La 0.8 The XRD spectrum of CoO3-MOF is as follows Figure 1 As shown, at 32° and 59°, the cerium-doped Ce 0.2 -La 0.8 CoO3-MOF has a single diffraction peak of the cubic phase, and the partial substitution of cerium forms a new crystal plane, which is more consistent with the cubic phase of lanthanum cobalt oxide (JCPDS No.75-0279) and different from the double diffraction peak of rhombohedral phase LaCoO3 (JCPDS No.84-0848). The substitution of cerium exceeds the solubility limit of lanthanum cobalt oxide perovskite, part of which is doped into the lattice of lanthanum cobalt oxide perovskite, and part of which is doped into the lattice of lanthanum cobalt oxide perovskite with CeO 1.675 exists on the surface of perovskite in the form of CeO 1.675 and Co3O4 impurity phase, forming CeO 1.675 / LaCoO3 composite perovskite oxide.

[0042] Sample Ce prepared in Example 1 0.2 -La 0.8 SEM images of CoO3-MOF are shown in Figure 2. Figure 2 As shown, Ce 0.2 -La 0.8 CoO3-MOF is a micron-elliptical structure assembled from tiny nanoparticles. It has a rough appearance, with many wrinkles and a quasi-hollow structure, which is beneficial for resisting sintering, improving mass transfer efficiency, and increasing the activity of the catalyst.

[0043] The pore structure parameters of each sample obtained in the above embodiments and comparative examples are shown in the following table:

[0044]

[0045]

[0046] The specific surface area of ​​the lanthanum-cobalt-based sample was increased through the MOF derivatization method, and the distributed pore diameter was about 6nm, which is larger than the kinetic diameter of toluene 0.6nm, which is conducive to the diffusion of toluene; and with the increase of cerium, the specific surface area, pore diameter and pore volume of the sample are increasing, providing more active sites and reducing mass transfer resistance.

[0047] like Figure 3The figure shows the results of toluene removal efficiency of each sample at different temperatures. The test was evaluated using a small fixed bed test bench. The sample amount was 0.1g, which was mixed with quartz sand and placed in a quartz tube with an inner diameter of 7mm. The initial toluene concentration was 1000ppm, and the gas volume space velocity (GHSV) was 25000h-1. The toluene concentration was monitored by a gas chromatograph equipped with an FID detector before and after the reaction. From the results, it can be seen that the improvement of sample performance by cerium doping is quite obvious. The lowest temperature (T 90 ) are all around 195°C, and commercial catalysts are generally above 230°C. However, excessive doping of cerium, such as the sample Ce prepared in Comparative Example 2 0.5 -La 0.5 CoO3-MOF, on the contrary, significantly reduced the performance (T 90 =210℃), the excessive cerium destroys the perovskite structure of LaCoO3. Although its pore structure parameters are relatively excellent, it cannot make up for the CeO 1.675 The synergistic effect of Ce / LaCoO3 improves the final performance; therefore, doping with a specific amount of Ce can achieve better performance.

[0048] Sample Ce prepared in Example 1 0.2 -La 0.8 The results of the removal efficiency of toluene by CoO3-MOF are shown in Figure 4 As shown, the reaction temperature is 210°C, and the other test conditions are the same as above. Figure 4 It can be seen that during the 20 hours of testing, the conversion rate of the sample for toluene was always higher than 90%, and there was no obvious decrease in catalytic activity.

[0049] In the present application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "middle", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings. These terms are mainly used to better describe the present invention and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation.

[0050] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a modified catalyst for catalyzing toluene combustion, characterized in that: The following steps are involved: Step S1, dissolving cobalt acetate tetrahydrate and lanthanum acetate tetrahydrate in 70 ml of ethylene glycol, adding urea, stirring for 30 minutes, and transferring to a hydrothermal kettle; keeping warm in an oven for a certain period of time, washing by ethanol centrifugation after cooling, and drying to obtain an intermediate; Step S2, mixing N,N-dimethylformamide, ethanol and water to obtain a mixed solution A; Step S3, adding the intermediate and 2,5-dihydroxyterephthalic acid to the mixed solution A and stirring, then adding cerium nitrate hexahydrate and performing ultrasonic dispersion to obtain a homogeneous mixed solution B; Step S4, transferring the homogeneous mixed solution B to a hydrothermal kettle, keeping it warm in an oven for a certain period of time, cooling it to room temperature, filtering and washing it with ethanol; after vacuum drying, sending it to a muffle furnace for calcination to obtain a catalyst sample Ce-LaCoO3-MOF.

2. The method for preparing a modified catalyst according to claim 1, characterized in that: In steps S1-S3, the molar ratio of cobalt acetate tetrahydrate, lanthanum acetate tetrahydrate, cerium nitrate hexahydrate, and 2,5-dihydroxyterephthalic acid is 1:(1-y):y:4:1 (y=0.1-0.3).

3. The method for preparing a modified catalyst according to claim 1, characterized in that: The amount of cobalt acetate tetrahydrate is 0.1 times the mass of the homogeneous mixed solution B.

4. The method for preparing a modified catalyst according to claim 1, characterized in that: In step S1, the oven is kept at 180°C for 12 hours.

5. The method for preparing a modified catalyst according to claim 1, characterized in that: In step S2, the volume ratio of N,N-dimethylformamide, ethanol and water is 8:1:

1.

6. The method for preparing a modified catalyst according to claim 1, characterized in that: In step S3, ultrasonic dispersion is performed for 30 minutes.

7. The method for preparing a modified catalyst according to claim 1, characterized in that: In step S4, the oven is kept at 130° C. for 24 hours.

8. The method for preparing a modified catalyst according to claim 1, characterized in that: In step S4, vacuum drying is performed at 70° C. for 12 hours, and calcination is performed at 400° C. for 6 hours.

9. A modified catalyst for catalyzing the combustion of toluene, suitable for being prepared by the preparation method of the modified catalyst according to any one of claims 1 to 8.

10. A modified catalyst for catalyzing the combustion of toluene, and its application in catalyzing the combustion of toluene at low temperature.

Citation Information

Patent Citations

  • Modified low-temperature SCO denitrification catalyst and preparation method thereof

    CN108262049A